Pengembangan Aplikasi Jurnalistik Berbasis Konten Lokal Bagi Masyarakat Umum - Aurelia Rante (Fakultas Teknologi Informasi, Universitas Atma Jaya Makassar, 2016)
Journalism-based application developmont of local content for the general public as a venue to accommadate to need to upload location-related news events around the domicile. Shortage on the utilization of the IP address as determining the location of visitor in determining the news obtained the reason the development of this application. The result of this research is application based journalism development local content has implemented the use of the geolocation of users on online journalism application uses the GPS feature. Geolocation data has been integrated into the structure of the application service journalism. GPS provides the coordinates of the location of the visitor so that the data can be displayed news about the location of website visitor